Sealant for liquid crystal dripping process, liquid crystal display panel using the same, and method of manufacturing liquid crystal display panel
Patent Information
- Application Number
- JP2023126176
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
Smart Images

Figure 2025021999000001 
Figure 2025021999000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealant for a liquid crystal dropping method, a liquid crystal display panel using the same, and a method for manufacturing a liquid crystal display panel. [Background technology]
[0002] A liquid crystal display panel for performing various displays usually has a pair of substrates, a frame-shaped sealant disposed between the substrates, and a liquid crystal material sealed within the area surrounded by the sealant. One of the methods for manufacturing such liquid crystal display panels is the liquid crystal dropping method.
[0003] In the liquid crystal dropping method, a liquid crystal sealant is applied to one of a pair of substrates by a dispense method to prepare a rectangular frame-shaped sealing pattern. Next, while the liquid crystal sealant is in an uncured state, a liquid crystal material is dropped into the frame-shaped sealing pattern and / or into the corresponding area of the other substrate. Then, the substrates are bonded together under vacuum, and the frame-shaped sealing pattern is irradiated with active energy rays such as ultraviolet rays to perform provisional curing. After that, the substrate is heated to perform main curing, and a liquid crystal display panel is prepared. As the liquid crystal sealant for such a liquid crystal display panel, many resin compositions containing a photocurable compound, a thermosetting compound, a photopolymerization initiator, and a thermosetting agent are known (for example, Patent Document 1). In addition, in order to increase storage stability and reduce contamination of the liquid crystal, it has also been proposed to use a photobase generator instead of a thermosetting agent (for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-102912 A [Patent Document 2] JP 2013-011881 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for manufacturing various products with low energy consumption in consideration of the environment, such as through decarbonization, and there is also a demand for liquid crystal display panels to be manufactured with even lower energy consumption.
[0006] For example, if the liquid crystal sealant can be cured only by irradiation with active energy rays during the manufacture of a liquid crystal display panel in the liquid crystal dropping method, energy consumption can be reduced and the process can be further simplified. However, if the thermosetting compound or the thermosetting agent is removed from the composition of the conventional liquid crystal sealant, it is difficult to achieve low moisture permeability of the resulting sealant, and defects may occur in the resulting liquid crystal display panel. In addition, defects may occur in terms of the adhesive strength between the substrate and the sealant. Furthermore, when various components are added to achieve the above adhesive strength and low moisture permeability, there is also a problem that these components bleed into the liquid crystal and contaminate the liquid crystal. In other words, it was difficult to design a liquid crystal sealant so that it can be cured only by irradiation with active energy rays.
[0007] The present invention has been made in view of the above problems, and aims to provide a sealant for the liquid crystal dropping method that is unlikely to contaminate liquid crystal, can be cured by irradiation with active energy rays, and can form a sealant that has high adhesive strength to a substrate and low moisture permeability, a liquid crystal display panel using the same, and a method for manufacturing a liquid crystal display panel. [Means for solving the problem]
[0008] The present invention provides a sealant for a liquid crystal dropping method, which comprises a curable compound, a photobase generator that generates a guanidine compound when irradiated with active energy rays, a photosensitizer, and a curing accelerator having an acid anhydride group, wherein the curable compound comprises an epoxy compound having an epoxy group.
[0009] The present invention further provides a liquid crystal display panel having a pair of substrates, a liquid crystal layer sandwiched between the pair of substrates, and a frame-shaped sealant disposed between the pair of substrates for sealing the liquid crystal layer, wherein the sealant is a cured product of the sealant for use in a liquid crystal dropping method.
[0010] The present invention further provides a method for manufacturing a liquid crystal display panel, the method including the steps of: preparing a pair of substrates; applying the above-mentioned sealant for the liquid crystal dropping method onto one of the substrates to form a frame-shaped sealing pattern; dropping a liquid crystal material onto the inside of the frame-shaped sealing pattern and / or onto a corresponding area of the other substrate while the frame-shaped sealing pattern is in an uncured state; and overlapping the pair of substrates with the liquid crystal material interposed therebetween, and irradiating the frame-shaped sealing pattern with active energy rays. Effect of the Invention
[0011] The sealant for the liquid crystal dropping method of the present invention is unlikely to contaminate liquid crystal and can be cured by irradiation with active energy rays. Furthermore, a sealing material obtained from the sealant for the liquid crystal dropping method has high adhesive strength to a substrate and low moisture permeability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] In this specification, a numerical range expressed using "to" means a range that includes the numerical values before and after "to" as the lower and upper limits.
[0013] 1. Sealant for liquid crystal dripping method The sealant for liquid crystal dropping method of the present invention (hereinafter, also simply referred to as "liquid crystal sealant") is a composition that can be cured by irradiation with active energy rays. In other words, it is a composition that can be cured without heating. In addition, examples of active energy rays in this specification include electron beams, ultraviolet rays, visible light, etc.
[0014] As described above, it is required to cure the liquid crystal sealant with less energy consumption. Therefore, for example, curing the liquid crystal sealant only by irradiation with active energy rays has been considered. However, when the liquid crystal sealant is designed to mainly contain radically polymerizable compounds, various problems tend to occur, such as high moisture permeability of the resulting sealant and insufficient adhesive strength between the sealant and the substrate. In addition, in order to solve such problems, it is possible to use an epoxy-based compound, but it is difficult to sufficiently cure the epoxy-based compound by irradiation with active energy rays, and contamination of the liquid crystal may occur.
[0015] In response to this, the inventors of the present invention have intensively studied and found that by using a photobase generator that generates a guanidine compound by irradiation with active energy rays, a photosensitizer, and a curing accelerator having an acid anhydride group together with a curable compound such as an epoxy compound, the liquid crystal sealant can be sufficiently cured only by irradiation with active energy rays. The sealing material obtained from the liquid crystal sealant has good adhesion to the substrate and low moisture permeability. The liquid crystal sealant also has the advantage of being less likely to contaminate the liquid crystal. The reason for this is unclear, but is thought to be as follows. The guanidine compound generated from the photobase generator by irradiation with active energy rays is a relatively strong base, and the guanidine compound reacts with the epoxy group of the epoxy compound. However, the reaction between the guanidine compound and the epoxy compound is relatively slow, and the epoxy compound (curable compound) is likely to be sufficiently cured only by these reactions. On the other hand, by further combining a curing accelerator having an acid anhydride group, the curing speed of the epoxy compound is increased, and the crosslinking density in the sealing material is increased by the reaction between the curing accelerator and the epoxy compound. As a result, it is considered that the components in the liquid crystal sealant are less likely to contaminate the liquid crystal, and the moisture permeability of the sealing material is reduced. In addition, the curing accelerator having an acid anhydride group makes the internal structure relatively rigid, so that the moisture permeability of the sealing material is very low. Each component of the liquid crystal sealing material of the present invention will be described below.
[0016] (1) Curable compound The curable compound may contain an epoxy-based compound having an epoxy group, and may contain a compound other than an epoxy-based compound, and may further contain a radically polymerizable compound having a radically polymerizable group, such as a (meth)acrylic compound. The type of radically polymerizable compound is not particularly limited, but a (meth)acrylic compound is preferred from the viewpoint of reactivity and the like. It is preferred to contain both an epoxy-based compound and a (meth)acrylic compound as the curable compound from the viewpoint of its curability and the strength of the resulting sealing material with the substrate. These compounds will be described below, but the curable compound is not limited to these. In this specification, (meth)acrylic means methacrylic, acrylic, and both. (meth)acryloyl means methacryloyl, acryloyl group, and both. (meth)acrylate means methacrylate, acrylate, and both.
[0017] Epoxy compounds In this specification, the epoxy compound may be a compound having one or more epoxy groups in the molecule, for example, a compound having an epoxy group and a (meth)acryloyl group (hereinafter also referred to as "(meth)acrylic modified epoxy compound"). The curable compound may contain only one type of epoxy compound, or may contain two or more types. It is preferable that the curable compound contains both a compound having an epoxy group and no (meth)acrylic group (hereinafter also referred to as "epoxy resin") and the above-mentioned (meth)acrylic modified epoxy compound. Each of these will be described below.
[0018] The epoxy resin in this specification may be a compound having one or more epoxy groups in one molecule (however, the (meth)acrylic modified epoxy compounds described below are not included in the epoxy resin). The curable compound may contain only one type of the epoxy resin, or may contain two or more types. The number of epoxy groups contained in the epoxy resin may be one or more, but is preferably two or more from the viewpoint of the curability of the liquid crystal sealant. Examples of the epoxy resin include known aromatic epoxy resins, aliphatic epoxy resins, and alicyclic epoxy resins. Among these, aromatic epoxy resins are preferred from the viewpoint of easily realizing low moisture permeability of the resulting sealant.
[0019] Examples of aromatic epoxy resins include aromatic polyhydric glycidyl ether compounds obtained by reacting epichlorohydrin with aromatic diols such as bisphenol A, bisphenol S, bisphenol F, bisphenol AD, and diols obtained by modifying these aromatic diols with ethylene glycol, propylene glycol, alkylene glycol, and the like; novolak-type polyhydric glycidyl ether compounds obtained by reacting epichlorohydrin with polyphenols such as novolak resins derived from phenol or cresol and formaldehyde, polyalkenylphenols, and copolymers thereof; and glycidyl ether compounds of xylylene phenol resins.
[0020] Among these, cresol novolac type epoxy resins, phenol novolac type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, triphenol methane type epoxy resins, triphenol ethane type epoxy resins, trisphenol type epoxy resins, dicyclopentadiene type epoxy resins, diphenyl ether type epoxy resins, and biphenyl type epoxy resins are preferred.
[0021] Here, the epoxy resin may be liquid or solid. From the viewpoint of easily realizing low moisture permeability of the sealing material, a solid epoxy resin is preferred. The softening point of the solid epoxy resin is preferably 40°C or more and 150°C or less. The softening point can be measured by the ring and ball method specified in JIS K7234.
[0022] The weight average molecular weight of the epoxy resin is preferably from 500 to 10,000, and more preferably from 1,000 to 5,000. The weight average molecular weight of the epoxy resin is measured by gel permeation chromatography (GPC) in terms of polystyrene.
[0023] The total amount of epoxy resin is preferably 5% by mass or more and 60% by mass or less, more preferably 10% by mass or more and 40% by mass or less, based on the total amount of curable compounds. If the amount of epoxy resin is 5% by mass or more, the moisture permeability of the encapsulant tends to be further reduced. On the other hand, if the amount of epoxy resin is 60% by mass or less, the amount of the (meth)acrylic compound described below increases, and the photopolymerization of the obtained encapsulant tends to be further improved.
[0024] On the other hand, a (meth)acrylic-modified epoxy compound, which is a type of epoxy compound, may have one or more epoxy groups and one or more (meth)acryloyl groups in the molecule. The curable compound may contain only one type of (meth)acrylic-modified epoxy compound, or may contain two or more types.
[0025] The number of epoxy groups and (meth)acryloyl groups in the (meth)acrylic modified epoxy compound is not particularly limited, and may be only one, or may be two or more. The (meth)acrylic modified epoxy compound has good compatibility with both the above-mentioned epoxy resin and the (meth)acrylic compound described below. Therefore, when the (meth)acrylic modified epoxy compound is included as a curable compound, the compatibility of different types of curable compounds tends to be good, and the liquid crystal sealant tends to be uniformly cured.
[0026] The (meth)acrylic modified epoxy compound is obtained by modifying at least one epoxy group of a compound having an epoxy group with a functional group of 2 or more with a (meth)acryloyl group. The (meth)acrylic modified epoxy compound is obtained, for example, by reacting an epoxy compound having a functional group of 2 or more with (meth)acrylic acid in the presence of a basic catalyst.
[0027] The epoxy compound modified with a (meth)acryloyl group may be a polyfunctional epoxy compound having two or more epoxy groups in the molecule, and from the viewpoint of suppressing excessive decrease in adhesive strength of the sealing material due to excessive increase in crosslink density, a bifunctional epoxy compound is preferred. Examples of bifunctional epoxy compounds include bisphenol type epoxy compounds (bisphenol A type, bisphenol F type, 2,2'-diallyl bisphenol A type, bisphenol AD type, and hydrogenated bisphenol type, etc.), biphenyl type epoxy compounds, and naphthalene type epoxy compounds. Among them, bisphenol type epoxy compounds of bisphenol A type and bisphenol F type are preferred from the viewpoint of improving the applicability of the liquid crystal sealant. The (meth)acrylic modified epoxy compound derived from the bisphenol type epoxy compound has an advantage of being superior in applicability compared to the (meth)acrylic modified epoxy compound derived from the biphenyl ether type epoxy compound.
[0028] In the (meth)acrylic modified epoxy compound, the ratio of the number of moles of (meth)acryloyl groups to the number of moles of epoxy groups is preferably 1 or more, and more preferably 2 or more. By increasing the ratio of the number of moles of (meth)acryloyl groups, it becomes easier to suppress the elution of the liquid crystal sealant into the liquid crystal.
[0029] The (meth)acrylic-modified epoxy compound preferably has a weight average molecular weight of 300 to 500 as measured by gel permeation chromatography (GPC).
[0030] The amount of the (meth)acrylic modified epoxy compound is preferably 10% by mass or more and 80% by mass or less, more preferably 15% by mass or more and 60% by mass or less, based on the total amount of the curable composition. When the amount of the (meth)acrylic modified epoxy compound is 10% by mass or more, the compatibility between the above-mentioned epoxy resin and the (meth)acrylic compound described below tends to be further improved. On the other hand, when the amount of the (meth)acrylic modified epoxy compound is 80% by mass or less, the obtained sealing material is more likely to achieve low moisture permeability and high adhesive strength.
[0031] (Meth)acrylic compounds In this specification, the (meth)acrylic compound refers to a compound having one or more (meth)acryloyl groups in the molecule, and does not include the above-mentioned (meth)acrylic modified epoxy compound (i.e., a compound having an epoxy group and a (meth)acryloyl group in one molecule). The curable compound may contain only one type of (meth)acrylic compound, or may contain two or more types. In addition, when the curable compound contains the (meth)acrylic compound, a photopolymerization initiator may be used in combination within a range that does not impair the purpose and effect of the present invention. The photopolymerization initiator may be the same as the photopolymerization initiator contained in a known liquid crystal sealant.
[0032] Here, the number of (meth)acryloyl groups contained in one molecule of the (meth)acrylic compound may be 1 or may be 2 or more. Examples of the (meth)acrylic compound containing one (meth)acryloyl group in one molecule include (meth)acrylic acid alkyl esters such as methyl (meth)acrylate, ethyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate.
[0033] Examples of (meth)acrylic compounds having two or more (meth)acryloyl groups in one molecule include di(meth)acrylates derived from polyethylene glycol, propylene glycol, polypropylene glycol, etc.; di(meth)acrylates derived from tris(2-hydroxyethyl)isocyanurate: di(meth)acrylates derived from a diol obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of neopentyl glycol; di(meth)acrylates (bisphenol A or F type epoxy(meth)acrylates) derived from a diol obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A or bisphenol F; di- or tri(meth)acrylates derived from a polyol obtained by adding 2 or 3 moles of ethylene oxide or propylene oxide to 1 mole of trimethylolpropane; di(meth)acrylates derived from a diol obtained by adding 4 or more moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A; tris( 2-Hydroxyethyl)isocyanurate tri(meth)acrylate;Trimethylolpropane tri(meth)acrylate or its oligomer;Pentaerythritol tri(meth)acrylate or its oligomer;Poly(meth)acrylate of dipentaerythritol;Tris(acryloxyethyl)isocyanurate;Caprolactone modified tris(acryloxyethyl)isocyanurate;Caprolactone modified tris(methacryloxyethyl)isocyanurate;Poly(meth)acrylate of alkyl-modified dipentaerythritol (meth)acrylate; poly(meth)acrylate of caprolactone-modified dipentaerythritol; hydroxypivalic acid neopentyl glycol di(meth)acrylate; caprolactone-modified hydroxypivalic acid neopentyl glycol di(meth)acrylate; ethylene oxide-modified phosphate (meth)acrylate; ethylene oxide-modified alkylated phosphate (meth)acrylate; and oligo(meth)acrylate of neopentyl glycol, trimethylolpropane, and pentaerythritol.Among these, di(meth)acrylates derived from diols obtained by adding 2 moles of ethylene oxide or propylene oxide to 1 mole of bisphenol A or bisphenol F (bisphenol A or F type epoxy(meth)acrylates) are preferred.
[0034] The weight average molecular weight of the (meth)acrylic compound measured by gel permeation chromatography (GPC) is preferably from 200 to 10,000, and more preferably from 200 to 5,000.
[0035] The weight average molecular weight of the (meth)acrylic compound is preferably about 310 to 1000. The weight average molecular weight is a value measured, for example, by gel permeation chromatography (GPC) in terms of polystyrene.
[0036] Here, the total amount of (meth)acrylic compounds is preferably 3% by mass or more and 60% by mass or less, more preferably 5% by mass or more and 40% by mass or less, based on the total amount of curable compounds. When the total amount of (meth)acrylic compounds is 3% by mass or more, the curability of the liquid crystal sealant tends to be further improved. On the other hand, when the total amount of (meth)acrylic compounds is 60% by mass or less, the amount of the epoxy compounds becomes relatively sufficient, and the adhesive strength and low moisture permeability of the obtained sealant tend to be further improved.
[0037] ·others The curable compound may further contain a curable compound other than those described above, as long as the object and effect of the present invention are not impaired.
[0038] Here, the total amount of the curable compounds is preferably 30% by mass or more and 85% by mass or less, more preferably 40% by mass or more and 75% by mass or less, based on the total amount of the liquid crystal sealant. When the total amount of the curable compounds is 30% by mass or more, the strength of the resulting sealant is sufficiently increased, and leakage of liquid crystal is easily suppressed. On the other hand, when the total amount of the curable compounds is 85% by mass or less, the amount of the photobase generator, photosensitizer, curing accelerator, etc. described below is sufficiently large, so that the curability of the liquid crystal sealant is further improved, and the viscosity of the liquid crystal sealant is easily within the desired range.
[0039] (2) Photobase generator The photobase generator may be a compound that is stable before irradiation with active energy rays and can generate a guanidine-based compound by irradiation with active energy rays. The photobase generator is a salt of a guanidine-based compound, and is ionized or has a molecule cleaved by irradiation with active energy rays to generate a guanidine-based compound. The liquid crystal sealant may contain only one type of photobase generator, or may contain two or more types.
[0040] Here, the guanidine-based compound in this specification may be any compound having a guanidino group, and may be a biguanide. The biguanide generated by the photobase generator is represented by the following general formula: [ka] In the above general formula, R 1 ~R 6 R each independently represents a hydrogen atom or a hydrocarbon group having 1 to 6 carbon atoms. The hydrocarbon group may be linear or branched, or may be cyclic. Furthermore, the hydrocarbon group may be saturated or unsaturated. 1 ~R 6 may be the same as or different from each other.
[0041] R 1 ~R 6Specific examples of R include linear hydrocarbon groups such as methyl, ethyl, propyl, butyl, and pentyl groups; branched hydrocarbon groups such as isopropyl, secondary butyl, and tertiary butyl groups; and cyclic hydrocarbon groups such as cyclopentyl, cyclohexyl, phenyl, and benzyl groups. 1 and R 2 are each preferably independently a branched hydrocarbon group such as an isopropyl group or a secondary butyl group, or a cyclic hydrocarbon group such as a cyclopentyl group or a cyclohexyl group. 3 ~R 6 are each preferably independently a straight-chain hydrocarbon group such as a methyl group, an ethyl group, a propyl group, a butyl group, or a pentyl group.
[0042] On the other hand, the type of compound that forms a salt with the guanidine compound is not particularly limited, and examples thereof include n-butyltriphenylborate, tetrakis(3-fluorophenyl)borate, 2-(3-benzoylphenyl)propionate, and the like.
[0043] Among these, it is more preferable that the compound generates radicals by irradiation with active energy rays, and among the above, n-butyl triphenyl borate is preferable. n-butyl triphenyl borate generates butyl radicals. When the photobase generator generates radicals by irradiation with active energy rays, the radicals function as a polymerization initiator for radical polymerization of (meth)acrylic compounds and the like in the curable compound. Therefore, it is possible to cure the liquid crystal sealant more efficiently.
[0044] The amount of the photobase generator is preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 1 part by mass or more and 5 parts by mass or less, based on 100 parts by mass of the curable compound. The amount of the photobase generator is preferably 0.05% by mass or more and 5% by mass or less, more preferably 0.5% by mass or more and 3% by mass or less, based on the total amount of the liquid crystal sealant. When the amount of the photobase generator is within this range, the epoxy compound in the curable compound and the guanidine compound react more easily, and the curability of the liquid crystal sealant tends to be further improved.
[0045] (3) Photosensitizers The photosensitizer is a compound for assisting the generation of the guanidine compound of the photobase generator by irradiation with active energy rays. The above-mentioned photobase generator may not be able to fully absorb active energy rays depending on the type and wavelength of the active energy rays. In contrast, the photosensitizer assists the generation of the guanidine compound, making it possible to efficiently cause the reaction between the guanidine compound and the epoxy compound. The photosensitizer may function not only as an assistant for the generation of the guanidine compound of the photobase generator, but also as a photopolymerization initiator.
[0046] The type of the photosensitizer is appropriately selected depending on the type of active energy rays to be irradiated. Specific examples of the photosensitizer include alkylphenone compounds (benzyl dimethyl ketal compounds such as 2,2-dimethoxy-1,2-diphenylethan-1-one (BASF, IRGACURE 651); α-aminoalkylphenone compounds such as 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one (BASF, IRGACURE 907); 1-hydroxy-cyclohexyl-phenyl-ketone (BASF, IRGACURE 907); 184) and other α-hydroxyalkylphenone compounds; acylphosphine oxide compounds such as 2,4,6-trimethylbenzoindiphenylphosphine oxide; titanocene compounds such as bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium; diethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, benzyl dimethyl ketal, 1-(4-isopropylphenyl)-2-hydroxy-2-methylpropan-1-one, 4-(2-hydroxyethoxy)phenyl-(2- acetophenone compounds such as 2-methyl-2-morpholino(4-thiomethylphenyl)propan-1-one, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone; phenylglyoxylate compounds such as methylphenylglyoxyester; benzoin ether compounds such as benzoin, benzoin methyl ether, and benzoin isopropyl ether; and oxime ester compounds such as 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyloxime)] (BASF, IRGACURE OXE01), ethanone-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-1-(O-acetyloxime) (BASF, IRGACURE OXE02);Benzophenone, o-benzoylbenzoic acid methyl-4-phenylbenzophenone, 4,4'-dichlorobenzophenone, hydroxybenzophenone, 4-benzoyl-4'-methyl-diphenyl sulfide, acrylated benzophenone, 3,3',4,4'-tetra(t-butylperoxycarbonyl)benzophenone, 3,3'-dimethyl-4-methoxybenzophenone and other benzophenone-based compounds; thioxanthone, 2-chlorothioxanthone (Tokyo Chemical Industry Co., Ltd.), 1-chloro-4-propoxythioxanthone, 1-chloro-4-ethoxythioxanthone (Lambson Limited, Speedcure CPTX), 2-isopropylxanthone (Lambson Limited, Speedcure ITX), 4-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone (Lambson Limited, Speedcure thioxanthone compounds such as DETX and 2,4-dichlorothioxanthone; anthraquinone compounds such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-t-butylanthraquinone, 1-chloroanthraquinone, 2-hydroxyanthraquinone (Tokyo Chemical Industry Co., Ltd., 2-Hydroxyanthraquinone), 2,6-dihydroxyanthraquinone (Tokyo Chemical Industry Co., Ltd., Anthraflavic Acid), and 2-hydroxymethylanthraquinone (Junsei Chemical Co., Ltd., 2-(Hydroxymethyl)anthraquinone); and benzyl compounds.
[0047] The absorption wavelength of the photosensitizer is appropriately selected depending on the type of active energy ray to be irradiated, but it is preferable that the photosensitizer has an absorption wavelength of 360 nm or more, more preferably has a maximum absorption wavelength in the visible light region, and even more preferably has a maximum absorption wavelength in the wavelength range of 360 to 430 nm. When the photosensitizer has a maximum absorption wavelength in this range, it becomes possible to cure the liquid crystal sealant by irradiation with visible light.
[0048] Examples of photosensitizers having an absorption wavelength of 360 nm or more include alkylphenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, thioxanthone compounds, and anthraquinone compounds, of which thioxanthone compounds are preferred.
[0049] The structure of the photosensitizer can be identified by combining high performance liquid chromatography (HPLC) and liquid chromatography mass spectrometry (LC / MS) with NMR or IR measurements.
[0050] The molecular weight of the photosensitizer is preferably, for example, 200 or more and 5000 or less. If the molecular weight is 200 or more, the photosensitizer is less likely to dissolve into the liquid crystal material. On the other hand, if the molecular weight is 5000 or less, the compatibility of the photosensitizer with the curable compound and the photobase generator is likely to be increased, and the curability of the liquid crystal sealant is likely to be good. The molecular weight of the photosensitizer is more preferably 230 or more and 3000 or less, and even more preferably 230 or more and 1500 or less.
[0051] The molecular weight of a photosensitizer can be determined as the "relative molecular mass" of the molecular structure of the main peak detected when analyzed by high performance liquid chromatography (HPLC).
[0052] Specifically, a sample solution is prepared by dissolving a photosensitizer in THF (tetrahydrofuran), and high performance liquid chromatography (HPLC) measurement is performed. The area percentage of the detected peak (the ratio to the total area of each peak) is then calculated to confirm the presence or absence of a main peak. The main peak is the peak with the highest intensity (the peak with the highest height) among all peaks detected at a detection wavelength characteristic of each compound (for example, 400 nm for thioxanthone compounds). The relative molecular mass corresponding to the peak apex of the detected main peak can be measured by liquid chromatography mass spectrometry (LC / MS).
[0053] The amount of the photosensitizer is preferably 1 part by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of the photobase generator. The amount of the photosensitizer is preferably 0.01% by mass or more and 5% by mass or less, more preferably 0.1% by mass or more and 1% by mass or less, relative to the total amount of the liquid crystal sealant. When the amount of the photosensitizer is within this range, the curing property of the liquid crystal sealant tends to be good. On the other hand, when the amount of the photosensitizer is within the above range, contamination of the liquid crystal is unlikely to occur, and a higher quality liquid crystal display panel is likely to be obtained.
[0054] (4) Curing accelerator The curing accelerator is a compound having an acid anhydride group and may be any compound capable of accelerating the curing of the above-mentioned epoxy compound. The liquid crystal sealant may contain one or more types of the curing accelerator, or may contain two or more types of the curing accelerator.
[0055] The number of acid anhydride groups contained in the curing accelerator may be one or more, but the acid anhydride equivalent is preferably 200 or less, more preferably 170 or less. When the acid anhydride equivalent is 200 or less, the probability of contact with the guanidine compound generated from the photobase generator is likely to increase, and they are likely to react. As a result, the curing property of the obtained sealing material is likely to be further improved. The acid anhydride equivalent is the value obtained by dividing the molecular weight of the curing accelerator by the number of acid anhydrides contained in the curing accelerator, that is, (molecular weight of the curing accelerator / number of acid anhydride groups in one molecule of the curing accelerator).
[0056] Examples of the curing accelerator include phthalic anhydride-based acid anhydrides, such as phthalic anhydride, 1,2,3,6-tetrahydrophthalic anhydride, hexahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, 4-methylhexahydrophthalic anhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride; succinic anhydride-based compounds, such as succinic anhydride, octenylsuccinic anhydride, tetrapropenylsuccinic anhydride, and butane-1,2,3,4-tetracarboxylic dianhydride; maleic anhydrides such as maleic anhydride; trimellitic anhydrides such as ethylene glycol bis-anhydrotrimellitate, glycerol bis-anhydrotrimellitate monoacetate; norbornene anhydrides such as methyl-5-norbornene-2,3-dicarboxylic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, bicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride, methylbicyclo[2.2.1]heptane-2,3-dicarboxylic anhydride.
[0057] The amount of the curing accelerator is preferably 0.5 parts by mass or more and 50 parts by mass or less, more preferably 5 parts by mass or more and 30 parts by mass or less, based on 100 parts by mass of the curable compound. The amount of the curing accelerator is preferably 0.1% by mass or more and 30% by mass or less, more preferably 3% by mass or more and 20% by mass or less, based on the total amount of the liquid crystal sealant. When the amount of the curing accelerator is within this range, the curing of the epoxy compound is easily promoted, and the curing property of the unreacted guanidine compound liquid crystal sealant is easily improved. On the other hand, when the amount of the curing accelerator is within this range, contamination of the liquid crystal is unlikely to occur, and a higher quality liquid crystal display panel is easily obtained.
[0058] (5)Other The liquid crystal sealant may contain components other than those described above, as long as the objects and effects of the present invention are not impaired. Examples of such components include inorganic fillers, core-shell type particles, silane coupling agents, various additives, etc.
[0059] Examples of inorganic fillers include calcium carbonate, magnesium carbonate, barium sulfate, magnesium sulfate, aluminum silicate, zirconium silicate, iron oxide, titanium oxide, titanium nitride, alumina other than the above, zinc oxide, silicon oxide (silica), potassium titanate, kaolin, talc, glass beads, sericite activated clay, bentonite, aluminum nitride, silicon nitride, etc. Among these, silica, alumina, and talc are preferred from the viewpoints of availability, stability, etc.
[0060] The shape of the inorganic filler may be regular, such as spherical, plate-like, or needle-like, or may be irregular. When the inorganic filler is spherical, the average primary particle size of the inorganic filler is preferably 1.5 μm or less. The specific surface area of the inorganic filler is preferably 0.5 m or less. 2 / g or more 20m 2 / g or less is preferable. The average primary particle size of the inorganic filler can be measured by the laser diffraction method described in JIS Z8825 (2013). The specific surface area of the filler is measured by the BET method described in JIS Z8830 (2013).
[0061] The amount of inorganic filler is preferably 10% by mass or more, more preferably 13% by mass or more and 30% by mass or less, based on the total amount of the liquid crystal sealant. If the content of inorganic filler is high, the moisture permeability of the resulting sealant tends to be low. However, if the content is too high, the applicability of the liquid crystal sealant decreases, so the above range is preferable.
[0062] On the other hand, core-shell type microparticles are microparticles having a core having desired physical properties and a shell covering the core. The shell can enhance compatibility with other components or cause partial reaction with other components.
[0063] Examples of core-shell type fine particles include organic fine particles having an elastic core containing conjugated diene rubber, silicone rubber, or the like, and a shell made of a polymer such as (meth)acrylate, vinyl monomer, or epoxy monomer.
[0064] Another example of the core-shell type microparticles includes microparticles having a core made of inorganic particles and a shell part made of a polymer layer covering the core, and having a functional group containing a carbon-carbon double bond on the surface. Examples of the functional group containing a carbon-carbon double bond that the core-shell type microparticles have include a vinyl group, an allyl group, an acrylic group, a methacrylic group, etc. Examples of the core in the core-shell type microparticles include the same particles as the inorganic filler. Among them, silica particles are preferable from the viewpoint of excellent thermal stability.
[0065] The liquid crystal sealing material may contain only one type of core-shell type fine particles, or may contain two or more types. The average primary particle diameter of the core-shell type fine particles is preferably 0.1 to 1.0 μm, more preferably 0.2 to 0.8 μm, and even more preferably 0.3 to 0.5 μm. The average primary particle diameter of the core-shell type fine particles can be determined by a microscopic method. Specifically, it can be measured by image analysis using an electron microscope. More specifically, the liquid crystal sealing material is subjected to image analysis, 50 organic fillers having a particle diameter of 1 μm or less are selected, and the average value of the particle diameters measured is taken as the average particle diameter.
[0066] The amount of the core-shell type fine particles is preferably 1% by mass or more and 12% by mass or less, more preferably 5% by mass or more and 10% by mass or less, based on the total amount of the liquid crystal sealant. When the content of the core-shell type fine particles is within this range, the physical properties of the resulting sealant can be more easily adjusted to the desired range.
[0067] Furthermore, the liquid crystal sealing material may further contain a silane coupling agent and various additives, if necessary.
[0068] Examples of the silane coupling agent include vinyltrimethoxysilane, γ-(meth)acryloxypropyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, and the like.
[0069] The amount of the silane coupling agent is preferably 0.5% by mass or more and 20% by mass or less based on the total amount of the liquid crystal sealant. When the content of the silane coupling agent is within this range, the adhesive strength between the obtained sealant and the substrate or alignment film tends to be further increased.
[0070] Examples of various additives include an ion trapping agent, an ion exchange agent, a leveling agent, a pigment, a dye, a sensitizer, a plasticizer, and an antifoaming agent.
[0071] Furthermore, the liquid crystal sealant may contain spacers and the like for adjusting the gap of the liquid crystal display panel.
[0072] The total amount of the various additives is preferably 1% by mass or more and 50% by mass or less, more preferably 1% by mass or more and 25% by mass or less, based on the total amount of the liquid crystal sealant. When the amount of the various additives is 50% by mass or less of the liquid crystal sealant, the viscosity of the liquid crystal sealant is unlikely to increase excessively, and the stability of the liquid crystal sealant is unlikely to be impaired.
[0073] As described above, the liquid crystal sealant of the present invention can be cured without heating. Therefore, it is not necessary to include a general heat curing agent. That is, in the liquid crystal sealant of the present invention, the amount of the heat curing agent (e.g., latent heat curing agent) is usually 10% by mass or less, preferably 5% by mass or less, and more preferably 1% by mass or less, based on the mass of the liquid crystal sealant.
[0074] (6) Physical properties of liquid crystal sealant The liquid crystal sealant of the present invention has a viscosity of preferably 200 to 450 Pa·s, more preferably 250 to 400 Pa·s, at 25° C. and 2.5 rpm as measured with an E-type viscometer. When the viscosity is within the above range, the liquid crystal sealant can be easily applied with a dispenser or the like.
[0075] Here, the liquid crystal sealant can be used as a liquid crystal sealant as described above. The liquid crystal sealant may contain only the liquid crystal sealant, or may be a mixture of the liquid crystal sealant and other components as necessary.
[0076] The liquid crystal sealant is mainly useful as a sealant for liquid crystal display panels, but is also useful as a sealant for display elements other than liquid crystal display panels, for example, organic EL elements and LED elements.
[0077] 2. Liquid crystal display panel and its manufacturing method (Liquid crystal display panel structure) The liquid crystal display panel of the present invention includes a pair of substrates, a pair of alignment films disposed between the pair of substrates, a liquid crystal layer sandwiched between the pair of alignment films, and a sealant for sealing the liquid crystal layer. The sealant is a cured product of the liquid crystal sealant described above.
[0078] Both of the pair of substrates are transparent. The material of the transparent substrate may be an inorganic material such as glass, or may be a plastic such as polycarbonate, polyethylene terephthalate, polyethersulfone, PMMA, etc. On the surface of each substrate, a matrix-shaped TFT, a color filter, a black matrix, etc. may be arranged.
[0079] Moreover, an alignment film is usually arranged on the inner side (liquid crystal layer side) of each substrate. The type of alignment film is not particularly limited, and includes films made of known organic alignment agents or inorganic alignment agents. The alignment film may be arranged so as to cover substantially the entire one surface of each substrate, that is, to extend from one end of the substrate to the other end. The alignment film may be arranged so as to cover only a part of the substrate, or may be arranged with a gap between the end of the alignment film and the end of the substrate.
[0080] Furthermore, the liquid crystal layer may be a layer made of a liquid crystal material sandwiched between the alignment films, and the type of the liquid crystal material is not particularly limited. The sealant is a frame-shaped structure disposed so as to surround the liquid crystal layer. In the liquid crystal display panel of the present invention, the sealant may be disposed so as to be sandwiched between the alignment films.
[0081] (Liquid crystal display panel manufacturing method) The liquid crystal display panel is manufactured by using the liquid crystal sealant of the present invention. Generally, there are two methods for manufacturing a liquid crystal display panel: a liquid crystal dropping method and a liquid crystal injection method. The liquid crystal display panel of the present invention is manufactured by the liquid crystal dropping method.
[0082] The method for manufacturing the liquid crystal display panel includes the steps of: 1) preparing two substrates on which alignment films are disposed; 2) applying the above-mentioned liquid crystal sealant onto the surface of one of the substrates on which the alignment film is formed, to form a frame-shaped sealing pattern; 3) dropping liquid crystal onto the inside of the frame-shaped sealing pattern of one of the substrates or onto the other substrate while the frame-shaped sealing pattern is in an uncured state; 4) superposing one substrate and the other substrate with liquid crystal therebetween; 5) irradiating the frame-shaped sealing pattern with active energy rays to harden it; Includes.
[0083] In the step 2), the area to which the liquid crystal sealant is applied is appropriately selected according to the desired structure of the liquid crystal display panel. The method of applying the liquid crystal sealant is not particularly limited as long as the liquid crystal sealant can be applied in a desired width, and can be applied, for example, by a dispenser.
[0084] On the other hand, in the step 3), the uncured state of the frame-shaped sealing pattern means a state in which the curing reaction of the liquid crystal sealant has not progressed to the gel point. In addition, when the liquid crystal is dropped onto the other substrate in the step 3), the liquid crystal is dropped so that it fits inside the frame-shaped sealing pattern when the two substrates are superimposed in the step 4).
[0085] In step 5), the frame-shaped sealing pattern is cured by irradiating with active light. The active energy rays to be irradiated are appropriately selected depending on the type of photosensitizer in the liquid crystal sealant, and light in the visible light region is preferable, for example, light with a wavelength of 370 to 450 nm is preferable. Light with the above wavelengths causes relatively little damage to the liquid crystal material and the driving electrodes. For irradiation with active light energy, a known light source that emits ultraviolet light or visible light can be used. For irradiation with visible light, a high-pressure mercury lamp, a low-pressure mercury lamp, a metal halide lamp, a xenon lamp, a fluorescent lamp, or the like can be used.
[0086] The amount of irradiation with the active energy rays may be sufficient as long as the curable compound is sufficiently cured. The irradiation time varies depending on the composition of the liquid crystal sealant, but is, for example, about 30 seconds to 10 minutes. EXAMPLES
[0087] The present invention will be specifically described below with reference to examples, but the scope of the present invention is not limited to the description of the examples.
[0088] 1. Material Preparation (curable compound) Bisphenol F type epoxy resin (Mitsubishi Chemical Corporation, YL983U) Acrylic modified epoxy compound (KSM, BAEM-50) Bisphenol A diacrylate ester (acrylic compound, Daicel-Allnex, Ebecryl 3700)
[0089] (Photobase Generator) 1,2-Dicyclohexyl-4,4,5,5-tetramethylbiguanidium = n-butyltriphenylborate (Fujifilm Wako Pure Chemical Industries, Ltd., WPBG300) 9-Anthrylmethyl N,N-diethylcarbamate (Fujifilm Wako Pure Chemical Industries, Ltd., WPBG018)
[0090] (Photosensitizer) 2,4-Diethylthioxanthone (SpeedCureDETX, Sartomer)
[0091] (Cure accelerator) Mixture of 4-methylhexahydrophthalic anhydride and hexahydrophthalic anhydride (manufactured by New Japan Chemical Co., Ltd., Rikacid MH700, acid anhydride equivalent: 161-166) Dodecenylsuccinic anhydride (manufactured by New Japan Chemical Co., Ltd., Rikacid DDSA, acid anhydride equivalent: 258-285)
[0092] (Inorganic filler) Silica particles (SO-C1, manufactured by Admatechs)
[0093] (Core-shell type particles) Fine particle polymer (F351, manufactured by Aica Kogyo Co., Ltd.)
[0094] (Silane coupling agent) ·Silane coupling agent (KBM-403, Shin-Etsu Chemical Co., Ltd.)
[0095] 2. Preparation of Sealant (Examples 1 to 6 and Comparative Examples 1 to 4) The curable compound, photobase generator, photosensitizer, curing accelerator, and other components were mixed in the mass ratios shown in Table 1 using a triple roll to obtain a sealant.
[0096] 3. Evaluation The obtained cured liquid crystal sealant was evaluated for adhesive strength, moisture permeability (moisture resistance), and liquid crystal contamination by the following methods. The results are shown in Table 1.
[0097] (Adhesive strength) The obtained liquid crystal sealant was applied using a dispenser (Shot Master, manufactured by Musashi Engineering Co., Ltd.) to a 38 mm × 38 mm square frame-shaped sealing pattern (cross-sectional area 2500 μm) on a 40 mm × 45 mm glass substrate (RT-DM88-PIN, manufactured by EHC Co., Ltd.) on which a transparent electrode and an alignment film had been previously formed. 2 ) was formed. Next, a pair of glass substrates was bonded to the glass substrate on which the frame-shaped sealing pattern was formed perpendicularly under reduced pressure, and then the pair of glass substrates was exposed to the atmosphere. The two bonded glass substrates were then held in a light-shielding box for 1 minute, and then exposed to 3000 mJ / cm 2 The specimen was then irradiated with light including visible light (light with a wavelength of 370 to 450 nm) to obtain a test piece. The corner of the frame-shaped sealing pattern of the obtained test piece was pressed vertically at a speed of 5 mm / min using a pressing tester (Model 210, manufactured by Intesco Co., Ltd.). This operation was performed on 10 glass substrates (n=10), and the number of glass substrates that were broken was counted. The adhesive strength was evaluated according to the following criteria. ◎: 8 to 10 glass substrates were broken ○: 3 to 7 glass substrates were broken △: 1 to 2 glass substrates were broken ×: 0 glass substrates were broken The more the number of broken glass substrates, the higher the adhesive strength is judged to be. △ or higher is at a level that is not problematic for practical use and is judged to be good.
[0098] (Moisture resistance) The obtained liquid crystal sealant was applied to a release paper with a thickness of 100 μm using an applicator. The applied liquid crystal sealant was then placed in a nitrogen replacement container and purged with nitrogen for 5 minutes, after which it was purged with 3000 mJ / cm 2 . 2 A cured film was produced by irradiating the sample with light (calibrated with a 365 nm wavelength sensor).
[0099] Two sheets of cured film were placed on an aluminum cup filled with calcium chloride (anhydrous) as a moisture absorbent, and an aluminum ring was placed on top and screwed in, after which the initial weight of the entire aluminum cup was measured. The aluminum cup was then placed in a thermostatic chamber set at 60°C and 90% Rh, and after 24 hours had passed, the aluminum cup was removed and its weight was measured. The obtained weight value was substituted into the following formula to calculate the moisture permeability. Calculation formula: Moisture permeability = (weight after test - weight before test) x film thickness / (film area x 100) And the evaluation was based on the following criteria: ◎: Moisture permeability is 60g / m 2 below ○: Moisture permeability is 60g / m 2 Super 80g / m 2 below △: Moisture permeability is 80g / m 2 Super 100g / m 2 below ×: Moisture permeability is 100g / m 2 Super If it was rated as △ or above, it was deemed to be at a level that would not cause any problems in practical use and was deemed to be good.
[0100] (Liquid crystal contamination) The liquid crystal sealant obtained in the examples and comparative examples was applied to a 40 mm × 45 mm glass substrate (RT-DM88-PIN, manufactured by EHC Corporation) on which a transparent electrode and an alignment film had been formed, using a dispenser (Shot Master, manufactured by Musashi Engineering Co., Ltd.) to form a 35 mm × 35 mm square main seal pattern (cross-sectional area 3500 μm 2 ) and a rectangular subseal pattern of 38 mm x 38 mm was formed around its outer periphery. Next, a liquid crystal material (MLC-7026-100, manufactured by Merck) in an amount equivalent to the liquid crystal content of the liquid crystal display panel to be obtained was precisely dropped into the frame of the main seal using a dispenser, and then left to stand for 5 minutes. Then, the above glass substrate and the glass substrate that will be paired with the above glass substrate were bonded together under a reduced pressure of 4 Pa, and then released to atmospheric pressure. After the two bonded glass substrates were held in a light-shielding box for 1 minute, the main seal was masked with a substrate on which a square black matrix of 36 mm x 36 mm was formed, and in this state, light with a wavelength of 370 to 450 nm was irradiated at 1 J / cm. 2 The glass substrate was irradiated with light at a rate of 1000 nm to cure the main seal, thereby obtaining a liquid crystal cell. Polarizing films were then attached to both sides of the obtained liquid crystal cell, thereby obtaining a liquid crystal display panel. The display characteristics of the obtained liquid crystal panel were evaluated according to the following criteria. ◎: The liquid crystal is aligned up to the edge of the main seal of the LCD panel, so there are no color unevenness or bright spots. ○: Color unevenness or bright spots occur over an area of less than 1 mm near the edge of the main seal ×: Color unevenness or bright spots occur over an area of 1 mm or more near the edge of the main seal If it was rated as ◯ or above, it was deemed to be at a level that would not cause any problems in practical use and was deemed to be good.
[0101] [Table 1]
[0102] As shown in Table 1 above, the sealant containing the curable compound, the photobase generator that generates a guanidine compound, the photosensitizer, and the curing accelerator having an acid anhydride group caused little liquid crystal contamination and could be cured only by irradiation with light. In addition, the sealing material from which the liquid crystal sealant was obtained had high adhesive strength with the substrate and good moisture resistance (Examples 1 to 6).
[0103] In contrast, when a photobase generator that does not generate a guanidine compound was used, the resulting sealant had low adhesive strength and insufficient moisture resistance (Comparative Example 1). It is believed that the compound (amine) generated by the photobase generator could not react sufficiently with the epoxy group of the epoxy compound. Furthermore, even when a photobase generator that generates a guanidine compound was used, when no curing accelerator was used, the resulting sealant had low adhesive strength to the substrate and insufficient moisture resistance (Comparative Example 2). The results of Comparative Example 2 suggest that even if a guanidine compound is generated by a photobase generator, the desired adhesive strength and moisture resistance cannot be obtained by only the reaction between the epoxy compound and the guanidine compound.
[0104] Furthermore, even if a photobase generator that generates a guanidine compound and a curing accelerator were used, when a photosensitizer was not used, the adhesive strength of the resulting encapsulant to the substrate was low and the moisture resistance was insufficient (Comparative Example 3). In this case, it is believed that without the photosensitizer, the guanidine compound was not sufficiently generated from the photobase generator.
[0105] Furthermore, even if a base generator that generates a guanidine compound was used, when a photosensitizer was not used and a curing accelerator having a relatively large acid anhydride equivalent was used, liquid crystal contamination occurred (Comparative Example 4). As described above, it is believed that without a photosensitizer, a guanidine compound was not sufficiently generated from the photobase generator, and when the acid anhydride equivalent was large, the reactivity was insufficient and a large amount of uncured components were generated. [Industrial Applicability]
[0106] According to the present invention, it is possible to obtain a liquid crystal sealant that can be cured only by irradiation with active energy rays without contaminating the liquid crystal, and can form a sealant that has high adhesive strength to a substrate and high moisture resistance, and therefore it is possible to manufacture a liquid crystal display panel with low energy consumption.
Claims
1. A curable compound; a photobase generator that generates a guanidine compound when irradiated with active energy rays; A photosensitizer; A curing accelerator having an acid anhydride group; Including, The curable compound includes an epoxy-based compound having an epoxy group. Sealant for liquid crystal dripping method.
2. The amount of the photobase generator is 0.1 parts by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the curable compound. The sealant for liquid crystal dropping method according to claim 1 .
3. The amount of the curing accelerator is 0.5 parts by mass or more and 50 parts by mass or less relative to 100 parts by mass of the curable compound. The sealant for liquid crystal dropping method according to claim 1 .
4. The amount of the photosensitizer is 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of the photobase generator. The sealant for liquid crystal dropping method according to claim 1 .
5. The curing accelerator has an acid anhydride equivalent of 200 or less. The sealant for liquid crystal dropping method according to claim 1 .
6. The curable compound further includes a radical polymerizable compound having a radical polymerizable group. The sealant for liquid crystal dropping method according to claim 1 .
7. A pair of substrates; A liquid crystal layer sandwiched between the pair of substrates; a frame-shaped sealant disposed between the pair of substrates for sealing the liquid crystal layer; A liquid crystal display panel having The sealing material is a cured product of the sealant for liquid crystal dropping method according to any one of claims 1 to 6. LCD display panel.
8. Providing a pair of substrates; A step of applying the sealant for a liquid crystal dropping method according to any one of claims 1 to 6 onto one substrate to form a frame-shaped sealing pattern; dropping a liquid crystal material onto the inside of the frame-shaped sealing pattern and / or onto a corresponding region of the other substrate while the frame-shaped sealing pattern is in an uncured state; a step of overlapping the pair of substrates with the liquid crystal material interposed therebetween, and irradiating the frame-shaped sealing pattern with active energy rays; A method for manufacturing a liquid crystal display panel, comprising:
Citation Information
Patent Citations
Sealing agent for liquid crystal dropping method, vertical conduction material, and liquid crystal display element
JP2011102912A
Sealing agent for liquid crystal display element, vertical conduction material, and liquid crystal display element
JP2013011881A